Analisis Kalimat pada Teks Biografi dalam Buku Cerdas Cergas Berbahasa dan Bersastra Indonesia untuk SMA/SMK Kelas X Kurikulum Merdeka - Citra Ajeng Cendekia; Diyah Dhariyanti; Khariztma Nuril Qolbi Barlanti; Feny Amanda Primasari; Asep Purwo Yudi Utomo; Dina Nurmalisa (Universitas Katolik Widya Karya Malang, 2023)
A grammatical arrangement has smaller constituents, namely sentences. This study aims to describe the types of sentences based on the number of clauses, modes, passive sentences, direct sentences, and negative sentences contained in the biographical text in the learning book entitled